Efektivitas Pelaksanaan Pemeriksaan Dalam Rangka Meningkatkan Penerimaan Negara dari Sektor Pajak (Studi kasus di KPP Pratama Mempawah) - B31108114, Pradito Waskitho (Jurnal Manajemen Update, 2013)
Calculation of effectiveness in terms of the settlement is calculated based on the issuance and realization of the Tax Inspection Warrant (SP3) is completed, the years 2010 had 152% effectiveness of the criteria is very effective. While the 2011 has the effectiveness of 147% which includes the criteria are very effective. While in 2012 has the effectiveness of 97% which includes the criteria are effective.The result of the effectiveness of the settlement in terms of acceptance of the results of which are calculated based on the realization of targets and inspection provisions, which in 2010 had 104% effectiveness of the criteria is very effective. While the 2011 has the effectiveness of 106% which includes the criteria are very effective. While in 2012 has the effectiveness of 105% which includes the criteria are very effective.SP3 includes successful completion because of KPP Pratama Mempawah SP3 can always finish within the allotted time is one year, although not resolved in every year but did not leave a lot of balance. Similarly, mean performance of the KPP Pratama Mempawah already well because it can meet the set targets, KPP Pratama Mempawah performance so far has been very professional, given the realization is over from what was targeted.Keywords :tax and effectiveness